Evaluating the effects of tunnel construction on buildings - Haji, Twana Kamal (2017)
New tunnels are continually constructed beneath the surface of large and developed cities due to the lack of surface space. These new tunnels will undoubtedly interact with existing surface and subsurface assets, such as building foundations, pipelines and other buried structures. There will be a two-way interaction whereby the tunnel construction affects the existing structure by inducing displacements in the underlying soil, and the structure influences tunnelling induced displacements via its weight and stiffness. The design of tunnels should include the consideration of this soil–structure interaction to avoid significant damage or failure to the existing structures due to the effect of the newly constructed tunnel. The research presented in this thesis focuses on tunnel–building interaction, and more specifically on buildings with shallow foundations. Previously, numerical methods have been used to study specific scenarios or to obtain design charts for use by geotechnical engineers. The proposed design charts have various limitations. For instance, they are suggested for specific types of soils, the 3D nature of buildings is disregarded to a great extent, and most importantly, several main parameters that influence the behaviour of a building when affected by tunnelling have not been accurately considered. In this research, the 3D behaviour of buildings is investigated with a focus on the main parameters that affect the deformation of a building in reality. These parameters are determined based on mathematical relationships of the stiffness of a structural member. Furthermore, computationally efficient methods are proposed to estimate building bending stiffness that can be readily used by engineers. The focus of this work is the effect of tunnelling on concrete framed buildings. The research deals with three main areas: [i] the estimation of the bending stiffness of a building’s superstructure and foundation, [ii] the analysis of tunnel–soil–building interaction using realistic ground displacements achieved from the field or experimental studies, and [iii] the behaviour of a 3D building (weightless and weighted) in a soil–building system during the construction of a tunnel. Finite element analysis (ABAQUS 3D) is used to investigate these problems. In research area [i], the building superstructure and the foundation are treated separately. Approaches are proposed in which the building response to tunnelling is related to the bending of a beam and empirical-type relationships are developed to predict building bending stiffness. These approaches are somewhat unconventional, but it is shown that they capture the real 3D response of buildings and foundations to tunnelling induced ground displacements more accurately than previously proposed methods. The approaches are relevant to scenarios where the building is perpendicular to the tunnel axis. Additionally, two cases of tunnel–building relative position are considered: (1) a case where a tunnel is constructed outside the building plan area (i.e. the tunnel axis and the nearest edge of the building to the tunnel do not overlap by more than half of the tunnel cross-section), which is called the ‘cantilever approach,’ and (2) a scenario where the tunnel is located under the building centreline, which is called the ‘fixed–ended approach.’ It should be noted that a detailed understanding of how structural elements of a building contribute to the stiffness of the entire building system is missing in the literature. The results of research area [i] show that the contribution of the building storeys to the global building bending stiffness is not uniform; the lower storeys have a larger contribution than the upper ones. Furthermore, buildings are mainly represented by 2D beams or frames in the current methods of building stiffness estimation. The proposed methods of this thesis (cantilever and fixed–ended methods) present accurate estimations of the true bending stiffness of 3D buildings subjected to tunnelling induced ground movements. In addition, the length of the building subjected to deflections, the length that is not affected by deformations, and the cross sectional flexural rigidity play the main role in the estimation of bending stiffness. These parameters are strongly interconnected, and should be considered together in the analysis of tunnel–building interaction. The results of this research show that the bending stiffness of a building decreases dramatically as the length affected by ground displacements increases. In contrast, the length of the building that is unaffected provides resistance to the building against rotation, which in turn increases the bending stiffness. This is because the unaffected length determines the boundary condition of the building, which is an important parameter in determining the bending stiffness. Research area [ii] aims to provide a method to overcome issues arising when using numerical analyses to investigate tunnelling and its impact on structures, since ground displacements predicted with conventional numerical methods are generally wider and shallower than those observed in practice. A two-stage numerical technique is proposed to estimate the effect of building stiffness on ground displacements due to tunnelling. In the first stage, greenfield (no existence of structures) soil displacements are applied to the soil model and the nodal reaction forces are recorded. In the second stage, the effect of tunnelling on a structure is evaluated by applying the recorded nodal reactions to an undeformed mesh. Results show that by using this technique, the role of the soil constitutive model is removed from the process of evaluating tunnelling induced ground displacements; it is only used in the evaluation of the soil–structure interaction. A realistic prediction of the structural stiffness effect can therefore be achieved due to the application of realistic ground displacements. For research area [iii], the response of weightless and weighted 3D buildings to tunnelling in a global soil–building system is considered. For the weightless case, the degree of stiffness contribution of the foundation and the superstructure to the bending resistance of the building is investigated. Buildings in the literature are assumed to act as a single entity when affected by tunnelling. Results of this research show that the effect of the foundation stiffness has the most significant contribution to the global building resistance to soil deformations while the contribution of the superstructure stiffness is less significant. Using insights from these results as well as those of research area [i], an equivalent beam method is proposed to model 3D buildings as 2D beams in plane strain analyses. The equivalent beam considers the effect of parameters influencing bending stiffness of a member, and the non-uniformity of stiffness contribution of building storeys to the global building bending stiffness. For the weighted buildings, a study is presented about the approach used to design a building, and the assumptions made in the analysis and design stages prior to the construction of a tunnel. The design parameters most affected by the tunnel construction are determined and examined numerically. It is explained that there is a strong relationship between the weight and bending stiffness of a building.